KEPUTUSAN PEMBELIAN PIZZA PAPA RON'S (Studi Kasus Pada Pondok Pinang Center Jakarta Selatan) - Fauzan Lailal Aziz (2020)
This research is a quantitative study that aims to determine the effect of Price, Product Quality, Sales Promotion on Purchasing Decisions. The study population was visitors to Papa Ron's Pizza Pondok Pinang Center, South Jakarta. The sample size was taken as many as 75 respondents, with non-probability sampling methods especially purposive sampling. Data collection is done through a questionnaire, especially Google Form. The analysis technique used is the PLS (Partial Least lSquare) method. The results of this study indicate that (1) Price has a significant iinfluence on purchasing decisions (2) Product Quality has an iinsignificant effect on Purchasing Decisions (3) Sales Promotion has a significant influence on Purchasing Decisions.